PEMBANGUNAN DAN MANAJEMEN APLIKASI UJIAN ONLINE BAGI MADRASAH SEBAGAI SOLUSI BERBAGAI PROBLEM YANG MUNCUL SAAT EVALUASI KEGIATAN BELAJAR MENGAJAR SISWA (Studi Kasus pada Madrasah Aliyah Negeri Kota Blitar dan Madrasah Aliyah Matholi'ul Anwar Karanggeneng - Arya Yudhi Wijaya; Agus Zainal Arifin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
One aspect of measuring the quality of teaching and learning is the processof students evaluation. During this process, teachers in secondary schools,especially madrasah which is identical to the conventional education systemcompared with public schools, have difficulty in performing the test especiallyin the correction process and cheating prevention. The proposed solution in thisservice is to build an online exam application in the computer laboratory formadrasah. With the application of this online system, the exam can beconducted in a computer network and can prevent cheating because thequestions and answers were randomized. In addition, the online exam is alsoeasier for the teacher to evaluate since there is a statistical report of testresults. Experimental results using online exam application at partner schoolhas shown some benefits, i.e. accelerating the implementation of exams forstudents, ensuring confidentiality matter, facilitate the supervision of the testimplementation, speed up the process of getting value without havingpreoccupied with the correction manually, speeding up the analysis of dailytests and questions analysis, and minimize the possibility of cheating. We stillfound obstacles in the field, namely the lack of quality infrastructure to supportthe use of online exams.Keyword: Computer Based Test, Online Test